ANALISIS KORELASI DAN KOEFISIEN LINTAS ANTAR BEBERAPA SIFAT PADI GOGO PADA MEDIA TANAH MASAM - Bakhtiar Bakhtiar; Bambang S. Purwoko; Trikoesoemaningtyas Trikoesoemaningtyas; Iswari S. Dewi (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2010)
A study was conducted to study correlation between some characters of upland rice and path coefficient analysis, which will be helpful for further selection process to improve upland rice in acid soils. The results of evaluation of lines for Al-tolerant in acid soils revealed that number of tillers and filled grain per panicle were inherited with high heritability and directly affected grain weight and contributed indirectly to the correlation between grain weight and other characters. However, indirect selection through number of tillers and filled grain per panicle was less efficient than direct selection through grain weight.